2013
DOI: 10.1371/journal.pgen.1003605
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Anatomical Basis of the Barrier Separating Wakefulness and Anesthetic-Induced Unresponsiveness

Abstract: A robust, bistable switch regulates the fluctuations between wakefulness and natural sleep as well as those between wakefulness and anesthetic-induced unresponsiveness. We previously provided experimental evidence for the existence of a behavioral barrier to transitions between these states of arousal, which we call neural inertia. Here we show that neural inertia is controlled by processes that contribute to sleep homeostasis and requires four genes involved in electrical excitability: Sh, sss, na and unc79. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 42 publications
(84 reference statements)
11
96
1
1
Order By: Relevance
“…Traditionally, this has been considered a pharmacokinetic phenomenon, but more recent data support the hypothesis that emergence from anesthesia is under distinct neurobiological control. [22][23][24] These findings bear on the present question. Even if we assume no difference in anesthetic sensitivity between demented and non-demented patients at the beginning of the anesthetic effect, there may nonetheless be significant differences at its end.…”
Section: Emergence From General Anesthesia Has Distinct Neurobiologysupporting
confidence: 54%
See 1 more Smart Citation
“…Traditionally, this has been considered a pharmacokinetic phenomenon, but more recent data support the hypothesis that emergence from anesthesia is under distinct neurobiological control. [22][23][24] These findings bear on the present question. Even if we assume no difference in anesthetic sensitivity between demented and non-demented patients at the beginning of the anesthetic effect, there may nonetheless be significant differences at its end.…”
Section: Emergence From General Anesthesia Has Distinct Neurobiologysupporting
confidence: 54%
“…Cela a été traditionnellement considéré comme étant un phénomène pharmacocinétique, mais des données plus récentes étayent l'hypothèse que l'émergence de l'anesthésie relève d'un contrôle neurobiologique distinct. [22][23][24] Ces constatations sont pertinentes pour la question présente. Même si nous supposons qu'il n'y a pas de différence de sensibilité aux anesthésiques entre les patients atteints de démence et les patients indemnes de MA au commencement de l'effet des anesthésiques, il pourrait néanmoins y avoir des différences significatives quand cet effet prend fin.…”
Section: L'émergence D'une Anesthésie Générale Répond à Des Caractériunclassified
“…Its mediation by dedicated brain circuitry therefore suggests that in clinical use GABA A -R active anesthetics substitute for the neurotransmitter GABA much as in endogenous pain control circuitry morphine substitutes for enkephalins and endorphins. It follows that the switching circuitry itself serves an adaptive functional role, presumably in the realm of natural sleep and perhaps also in the realms of syncope (fainting), anti-predator immobility and concussion (Franks, 2008;Hayes et al, 1984;Joiner et al, 2013;Sandoval-Herrera et al, 2011). If so, MPTA neurons might contribute to state switching in these functions as well.…”
Section: Discussionmentioning
confidence: 99%
“…17,44,50,53,54 Studies across phyla as distinct as invertebrates and mammals have demonstrated that anesthetic drugs are capable of activating endogenous sleep-promoting neural systems. 18-22,55,56 Hence, we believe that exploring the commonalities and recognizing the key differences in the genesis of these states will be critical to advance our understanding both of anesthetic mechanisms as well as sleep neurobiology.…”
Section: Discussionmentioning
confidence: 99%
“…22 Studies in drosophila have shown that mutations in single genes can lead to large changes in sleep as well as crucial alterations in anesthetic sensitivity. 55,77 Moreover, increased synaptic activity specifically in sleep-related drosophila neurons alters responsiveness to isoflurane, unveiling a common neural pathway for sleep and anesthetic sensitivity. 56 However, circuits and genes affecting sleep do not exclusively map onto those regulating anesthetic responsiveness, as demonstrated by our results with halothane in the MnPO.…”
Section: Discussionmentioning
confidence: 99%